Pertanggungjawaban Hukum Dokter terhadap Pasien di Instalasi Kamar Bedah - Sucinta Ardianto (Majelis: Jurnal Hukum Indonesia, 2024)
With the increasing need for medical services and developments in technology, doctors and patients are often faced with various legal issues related to health care. The role of doctors in society is crucial because of the knowledge and skills needed to diagnose and treat disease, as well as maintain patient health. A surgeon is a specialist doctor who treats diseases, injuries or emergency conditions in the body through surgical methods (operatives) carried out in the operating room installation. The doctor's legal responsibility towards patients in the operating room installation is based on several relevant legal principles, the principle of informed consent or consent in treatment is an important factor in determining whether the doctor is responsible or not. Patients must be given adequate information about the diagnosis, procedures, risks, and treatment alternatives before giving consent for medical treatment. What are the rights and obligations between the doctor and patient in the agreement before surgery, as well as the agreement between the doctor and patient after the patient has received this information. Research methods using normative law are methods used to study legal rules as a system that can be linked to certain legal events. Secondary data uses tertiary legal data, secondary legal data and tertiary legal data from books, literature, publications and statutory sources related to all discussions. From this research it was found that every human being has the human right to live a healthy life and a doctor has ethical and professional responsibilities in carrying out his duties. The relationship between doctors and patients is regulated by applicable laws and regulations. It can be concluded that the legal responsibility of doctors towards patients in operating rooms is very important in medical practice. As health professionals, physicians have an ethical and legal obligation to provide safe, competent, and responsible care to their patients. If a doctor fails to meet expected standards of care or commits negligence that results in injury or harm to a patient, they may be legally liable.